2014
DOI: 10.1002/2013jc009535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating CMIP5 simulations of mixed layer depth during summer

Abstract: The ability of CMIP5 models in simulating surface mixed layer depth (MLD) during summer is assessed using 45 climate models. Their ocean models differ greatly in terms of vertical mixing parameterizations and model configurations. In some models, effects of surface waves, Langmuir circulations, submesoscale eddies, as well as additional wind mixing are included to improve upper-ocean simulation. Similar to findings by previous studies, the summer MLDs are significantly underestimated in most of the models. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 71 publications
3
39
1
Order By: Relevance
“…However, in contrast to the winter, ACCESS-ESM1 appears to systematically underestimate MLDs in the high-latitude ocean in summer, 60 % (or 30-40 m) in the Southern Ocean, Pacific and Atlantic oceans. In the Southern Ocean, in particular, the underestimation of summer MLDs is consistent with Sallée et al (2013) and Huang et al (2014), who showed that most CMIP5 models underestimate summer MLDs. Huang et al (2014) attributed this to a lack of vertical mixing in CMIP5 rather than sea surface forcing related to individual models, this is consistent with Downes et al (2015), who showed that these biases are also present in the ocean-only simulations of ACCESS-ESM1.…”
Section: Sea Surface Temperature and Mixed Layer Depthsupporting
confidence: 84%
“…However, in contrast to the winter, ACCESS-ESM1 appears to systematically underestimate MLDs in the high-latitude ocean in summer, 60 % (or 30-40 m) in the Southern Ocean, Pacific and Atlantic oceans. In the Southern Ocean, in particular, the underestimation of summer MLDs is consistent with Sallée et al (2013) and Huang et al (2014), who showed that most CMIP5 models underestimate summer MLDs. Huang et al (2014) attributed this to a lack of vertical mixing in CMIP5 rather than sea surface forcing related to individual models, this is consistent with Downes et al (2015), who showed that these biases are also present in the ocean-only simulations of ACCESS-ESM1.…”
Section: Sea Surface Temperature and Mixed Layer Depthsupporting
confidence: 84%
“…In particular, the parameterisation designed by Fox-Kemper et al (2011) to improve the mixed layer representation (present in the models marked with a black bullet point, Table 2) does not consistently result in better performances than those models without the parameterisation. This lack of relationship between MLD biases and vertical mixing parameterisation was already found by Huang et al (2014) for the summer MLD.…”
Section: Heat and Saltsupporting
confidence: 56%
“…Without BRP, the different criteria in the model agree within 10 m at the winter maximum, and overestimate the MIMOC value by 10 to 25 m. Summer minima, on the other hand, are constantly underestimated. This latter bias, common in current climate models and possibly caused by a poor or missing representation of mixing processes like surface waves and Langmuir circulations (Huang et al, 2014), is beyond the scope of the present paper. When the BRP is introduced, the gap widens between the MLDs obtained from the three criteria in the model.…”
Section: Arctic Oceanmentioning
confidence: 86%